The Ovulatory response of Beef and Dairy cows subjected to two follicular emergence synchronization protocols before superovulation - GONZÁLEZ–RAMOS, M A; ÁNGEL–GARCÍA, O; VELIZ–DÉRAS, F G; GAYTÁN–ALEMÁN, L R; GUILLEN–MUÑOZ, J M; CORRALES, A SOLÍS; GUERRERO–GALLEGO, H Z; MORALES–CRUZ, J L (The Indian Journal of Animal Sciences, 2023)
The aim of this study was to evaluate the superovulation response of Beef and Dairy donor cows to two differentfollicular emergence synchronization protocols. Twenty-two beef and dairy cows were divided into two groups viz.Conventional group (n=8) having four Holsteins and four Charolais cows between days 10 and 11 of their estrouscycle and IVD+EB group (n=14) with six Holsteins and eight Charolais cows treated with an intravaginal device (IVD) containing 1.9 g of P4 + 2 mg of estradiol benzoate (EB) between days 10 and 11 of their estrous cycle. The superovulation protocol consisted of intramuscular application of FSHp twice a day for four days, in decreasing doses (850 IU for Dairy cows and 500 IU for Beef cows). The number of follicles (13±1.1 vs. 7.5±0.9) and embryoscollected (11.7±2.1 vs 6.1±1.0) were significantly affected by the treatment in the Beef cows but, the protocols didnot significantly affect these variables in Dairy cows (12.2±0.9 vs 10.4±0.7, respectively). Regarding the productionof non-viable embryos, a significant difference was only found in the group of Beef cows for both treatments (8.2±2.3 vs. 1.3±0.3, respectively). Results showed that IVD+EB is not necessary for the superstimulation of the emergence of a new follicular wave before superovulation when it starts in the mid-luteal phase of the estrous cycle in Holstein cows and beef cows, since they had similar results without significant differences between both treatments.